Type 2 Diabetes From Pathophysiology to Cyber Systems - Pantea Stoian, Anca (IntechOpen, 2021)
Diabetes mellitus is a metabolic disease characterized by chronic high blood glucose levels. Of the various types of diabetes, type 2 diabetes is increasing in prevalence due to obesity, aging, sedentarism, and other factors. This book presents a novel approach to preventing and treating type 2 diabetes. Chapters cover such topics as diagnosis, pathogenesis, management, lifestyle and nutritional intervention, and systems to support early diagnosis and prevention of prediabetes.